Algebras generated by special symmetric polynomials on $\ell_1$ - Jawad, F.; Karpenko, H.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2019)
Let $X$ be a weighted direct sum of infinity many copies of complex spaces $\ell_1\bigoplus \ell_1.$ We consider an algebra consisting of polynomials on $X$ which are supersymmetric on each term $\ell_1\bigoplus \ell_1.$ Point evaluation functionals on such algebra gives us a relation of equivalence `$\sim$' on $X.$ We investigate the quotient set $X/\sim$ and show that under some conditions, it has a real topological algebra structure.